Understanding right-wing populists’ anti-abortion politics in Turkey: The symbolic violence of the state - Kutun, Melehat (Intersections. East European Journal of Society and Politics, 2024)
This study investigates how symbolic violence is shaping anti-abortion stances associated with legitimising right-wing populist policies. The prominent questions are as follows: What are the institutional and politico-administrative mechanisms that are impacting anti-abortion politics in terms of material and symbolic violence? How and to what extent does anti-abortion politics influence the interplay between symbolic and material state violence? The study argues that reproduction-centred policies and material and symbolic violence have intensified through anti-abortion politics in the discursive context of the social reproduction crisis in Turkey. It explores the institutional actions and the legitimation mechanisms of anti-abortion policies in relation to the penetration of right-wing populist politics after the authoritarian turn of 2010. This qualitative case study uses critical discourse analysis. It interprets the public speeches of representatives of the government and documentary data concerning the ruling party’s programmes, development plans and relevant legislation. The research provides a gendered perspective on the anti-abortion policies that anchor right-wing populism in terms of the crisis of social reproduction. It also contributes to critical state theory and pre-existing feminist scholarship on right-wing populism.